Numerical analysis of geometrical and aerodynamic enhancements of a birdlike wing. Issue 1 (2nd March 2015) - Harik, Ramy; Nicolas, Alipio; Dassouki, Mohamed; Bernard, Alain
Abstract : Purpose: – Biomimetic study existing natural biological elements to produce engineering products with similar performance and abilities. The purpose of this paper is to highlight biomimetic studies to produce a new type of airplanes: adding remiges, bending ability and flapping mechanisms. Design/methodology/approach: – The used methodology was to thoroughly investigate the literature, to define the proper endurance and fatigue parameters, to perform a series of numerical studies and report improvement percentages relevant to defined parameters. Findings: – By adding remiges and the bending mechanism, the authors managed to reach – numerically – the preset desired structure goal. Efficiency increased using remiges with less drag force. In addition, with the help of the bending wing technique, the drag force was improved. The flapping mechanism showed high vibration rates. Last but not least, applying multiple winglets gave a better optimization of the endurance parameter. Research limitations/implications: – Research is conducted at a university without any research facilities. No laboratories exist, and acquiring research papers is mostly difficult and costly. Originality/value: – The research study is original in the sense of its numerical investigation. Proposing biomimetic was at the heart of the airplane invention and cannot be stated as an original contribution. Rather the field has been recently abandoned, and performing this major literature review can be considered as original in a sense it summarizes recent to somewhat old advancement.